Fire resistance analysis of beams in multi-storey reinforced concrete institutional building - Loh, Ciao Xin (2019)
Fire analysis is currently incorporated into building modelling practice to evaluate the performance of a high-rise building against fire. Before that, most of the buildings did not incorporate these practices into account as they think that fire accident will never be happened on them as the probability of fire accident to take place is too low. However, they have started to focus in this topic since the incident 911 had occurred. Following by that, the researchers pointed out that there is a must to incorporate fire practices into the construction of buildings. Thus, this study is carried out to evaluate the effect of fire on beams of fire room during different fire duration. The model designed is a 4 stories tall institutional building in UTAR Kampar, Perak. Throughout this study, Eurocode is followed in the structural and fire design of building and suggested a target reliability index, βtarget of 3.8 as a guidelines of structural safety for 50 years design period. Two methods of structure reliability analysis methods are proposed to evaluate the reliability index of structure under fire.